Implementation Marketing Plan For Mining Contractor Service Company In Indonesia: English - Septiani, Jelita; Kustiawan, Unggul (Muhasabatuna : Jurnal Akuntansi Syariah, 2023)
Mining contractor service business in Indonesia is still one of the businesses that is quite competitive. The ministry of energy and mineral resources ( ESDM) notes that production in Indonesia is increasing every year. Indonesia’s coal production will increase from 2020-2021 to reach 7,2 %, based on the increase in the value of this coal production. PT. ANP, our company is very confident that our mining services business will grow. Of course, to be a better company than our competitors, our company must be able to provide added value to our customers in order to meet the needs of our customers. To be able to survive in the long term in the mining services business, our company will carry out a marketing strategy by starting our business by working with companies that are georgraphically established, owners, and mining areas that are not categorized as difficult access and high risk. Our company is also a mining contractor service company with  a medium-scale level that produces coal between 50,000-200,000 tons per month, this is also one of the advantages for our customers to choose us as partners because in medium-scale companies our rate are cheaper. Method is using STP and Marketing Mix ( NICE and 7 P ) strategies. This analysis can help mining contractor service companies in Indonesia use their marketing strategy.